PERAN KEPEMIMPINAN DALAM INSEMINASI DAN PENERAPAN “INVICTUS” DALAM BUDAYA ORGANISASI GERAKAN CREDIT UNION KELING KUMANG - AS, Adil Bertus; Putra, Masri Sareb; Elvi, Fitria; Junianta, Maria (Jurnal Bina Manajemen, 2023)
The article discusses the crucial role of leadership in disseminating and implementing the core philosophy and values of "Invictus" within the Keling Kumang Credit Union Movement (GCUKK). This philosophy has become a guide for members and leaders to make decisions and act in line with core values such as integrity, innovation, and togetherness. The significance of leadership's role in instilling these values is evident through continuous education and the example set by leaders for the members. They are not merely educators but also role modelsin embodying the "Invictus" values in their daily actions. Leaders play a pivotal role in shaping a strong and convincing organizational culture. Leadership's role also encompasses integrating the "Invictus" values into decision-making and organizational actions. Leaders face challenges and opportunities guided by these principles, ensuring alignment between values and practical execution. Recognition and acknowledgment by leaders towards members who adopt these values serve as a trigger for inspiration. This uplifts not only the spirits of the members but also encourages personal growth and contributions in the spirit of the "Invictus" values. The leadership's role in instilling and applying "Invictus" asa deeply rooted identity within GCUKK creates a robust culture, leading towards a future that is impactful and positive. Overall, the article underscores the vital role played by leadership in shaping an organizational culture that reflects the core values of the "Invictus" philosophy